Al2O3 and TiO2 flux enabling activated tungsten inert gas welding of 304 austenitic stainless steel plates (Fracture and Structural Integrity, 2022)
Gas tungsten arc welding (GTAW) is important in those manufacturing where it is significant to control the mechanical and metallurgical characteristics and its weld bead geometry. This work has been committed to study the influence of oxide fluxes on welding of 4 mm thick 304 austenitic stainless steel plates. The Al2O3 and TiO2 were used as an oxide flux in powder form and are mixed with the acetone. The prepared mixture is applied on bead plate without any joint preparation and without filler wire addition. The Taguchi method with L9 orthogonal array is used to determine the optimal parameters. The current work aims to explore the influence of weld parameters on weld bead geometry (i.e. weld bead width, penetration and angular distortion), and mechanical & metallurgical characteristics for 304 stainless steel welds. The oxide flux seems to narrow the arc and thereby the current density increases at the anode spot, that results in high weld depth.
Keywords: ATIG; Oxide flux; 304 stainless steel; Weld morphology; Angular distortion; Mechanical characteristics